Obesity, adipokines and neuroinflammation. (September 2015) - Aguilar-Valles, Argel; Inoue, Wataru; Rummel, Christoph; Luheshi, Giamal N.
Abstract: Global levels of obesity are reaching epidemic proportions, leading to a dramatic increase in incidence of secondary diseases and the significant economic burden associated with their treatment. These comorbidities include diabetes, cardiovascular disease, and some psychopathologies, which have been linked to a low-grade inflammatory state. Obese individuals exhibit an increase in circulating inflammatory mediators implicated as the underlying cause of these comorbidities. A number of these molecules are also manufactured and released by white adipose tissue (WAT), in direct proportion to tissue mass and are collectively known as adipokines. In the current review we focused on the role of two of the better-studied members of this family namely, leptin and adiponectin, with particular emphasis on their role in neuro-immune interactions, neuroinflammation and subsequent brain diseases. This article is part of a Special Issue entitled 'Neuroimmunology and Synaptic Function'. Highlights: Adipokine levels are altered during obesity and contribute to associated diseases. Leptin is considered pro-inflammatory, adiponectin an anti-inflammatory adipokine. Leptin accesses the brain and modulates acute and chronic inflammatory responses. Inflammation due to obesity contributes to psychiatric disorder pathophysiology. Leptin induces depression-like behavior via immune cell transmigration to the brain.